Уравнения метода граничных элементов в динамической пространственной задаче о трещине на поверхности раздела упругих сред - Меньшиков, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The paper is devoted to the boundary integral equations of elasticity theory for an interface crack between two elastic half-spaces under harmonic loading. The direct boundary elements method was used to derive a system of linear algebraic equations.